Corrosion Control of Coated Structural Components in Marine Environment - Manjunath, G L; Surendran, S (Sustainable Marine Structures, 2019)
Tropical waters are with more salinity and harbor millions of micro organisms. Such environmental condition challenges the strength and reliability of marine structures. The behaviour of structural materials due to pitting and uniform corrosion is studied, and a method based on coating is suggested to improve the life cycle ensuring reliability in its functionality. The structural materials like high strength steel and AA6063 were selected for the study and metallic coating performed for evaluation of corrosion resistances. Samples are investigated in chloride concentration of 3.5% NaCl by weight loss measurements and potentiodynamic polarization. The coating was done by electroplating and PVD (Physical Vapour Deposition) method for high strength steel, where as aluminum samples were coated by an electroplating method. The high strength steel samples were mono coated by Ni and Cr using the electroplating method, and composite coating was done with Al-N (Aluminium nitride) and Ti-Al-N (Titanium Aluminium Nitride) by PVD techniques. Scanning electron microscopy (SEM) was used for evaluation of fracture toughness of coating around the pits formed. The investigation showed that the methods and thickness of coating influenced corrosion resistances of the substrate metals. Composite coated samples by PVD showed excellent corrosion resistance properties compared to electroplated samples after the investigations. Finite element analysis was performed by FRANC 2D/L (Fracture Analysis Code) showed a decrease in stress intensity values for composite coated samples of PVD compared to mono coated electroplated samples. Increase in the duty cycle of the structure was observed in the simulation has a result of a decrease in stress intensity values for PVD coated samples. ER